2005
DOI: 10.1093/ndt/gfh1105
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal dialysis in refractory end-stage congestive heart failure: a challenge facing a no-win situation

Abstract: Peritoneal dialysis appears to be a promising therapeutic tool for patients affected by refractory CHF. Clinical improvement of cardiac function may be related to clearing blood from middle molecular weight myocardial depressant substances, including atrial natriuretic peptide. Prospective multicentre trials are needed to confirm these encouraging results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
90
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(102 citation statements)
references
References 13 publications
9
90
1
2
Order By: Relevance
“…Those needs have led to the use of a variety of techniques: a single night-long exchange; two daily exchanges; or automated PD 2 -4 nights per week. Criteria for starting PUF have also varied, but a frequent indication has been the number of hospital admissions for acute decompensated HF in the preceding year (15)(16)(17).…”
mentioning
confidence: 99%
“…Those needs have led to the use of a variety of techniques: a single night-long exchange; two daily exchanges; or automated PD 2 -4 nights per week. Criteria for starting PUF have also varied, but a frequent indication has been the number of hospital admissions for acute decompensated HF in the preceding year (15)(16)(17).…”
mentioning
confidence: 99%
“…These mediators whose molecular weight ranges between 500 and 30000 Dalton can penetrate from the peritoneal membrane, by this way PD allows clearance of these agents while contributing to the support for the heart directly (46,47).…”
Section: Why Peritoneal Dialysis Is Chosen In the Treatment Of Heart mentioning
confidence: 99%
“…Patient's preference as well as the clinical situation determines primarily the choice of UF for night or day and instrumental or manual methods. It has been shown that the rate of infection was lower with the use of single change instead of multiple changes (42,47,68,82). Especially in patients with residual renal function, the use of 'icodextrin', which provides long-term UF and allows single change, appears to be a more practical and appropriate option.…”
Section: Peritoneal Dialysis Catheter Placement Procedures and Peritonmentioning
confidence: 99%
“…Unfortunately, they are uncontrolled and the groups studied are small. Patients with coexisting renal failure may be treated with intermittent PD [21], continuous ambulatory PD [22][23][24][25][26] or automated PD [27][28][29][30], while in those without significant impairment of renal function -a single nightly exchange (PUF) with osmotic agent (optimally icodextrin) is sufficient [31][32][33][34][35]. In the vast majority of cases PD/PUF was performed in patients with advanced CHF and symptoms of cardiorenal syndrome as an addition to standard therapy.…”
Section: Peritoneal Ultrafiltrationmentioning
confidence: 99%
“…It usually concerned elderly patients with numerous comorbidities and various degrees of renal impairment, disqualified from heart transplantation and refractory to pharmacological treatment. In some centers, extracorporeal UF was initially performed for quick reduction of fluid overload [28,29,[32][33][34][35], while in the others therapy was commenced with PUF or PD. PUF/PD dose was matched to individual patient's needs in order to obtain optimal UF on one hand, while achieving adequate balancing of metabolic disturbances associated with renal impairment on the other.…”
Section: Peritoneal Ultrafiltrationmentioning
confidence: 99%